New technologies in tourism: a bibliometric reviewof research trends and emerging topics - Roman, Michał; Iaromenko, Sergii; Kawęcki, Norbert; Kudinova, Iryna; Szczucka, Ewa (Turystyka i Rozwój Regionalny, 2025)
The rapid growth of digital technologies is affecting all areas of life, including tourism.The ways in which people plan trips, experience places and engage with the tourism industryare evolving. As a result, increasing attention is being paid to the role of new technologiesin shaping modern tourism. The purpose of this article is to identify major trends, researchtopics and gaps in the literature on the application of new technologies in tourism, basedon a bibliometric review of publications. A state-of-the-art type review was conducted usingbibliometric analysis. The analysis included 296 publications from the Web of Science CoreCollection database (2000–2024), using the bibliometrix tool. Since 2019, a marked increasein publication volume has been observed. Research in the social, economic and environmentalsciences dominates. The most common topics are AI, big data and destination management.The largest number of publications comes from Spain. New technologies are changing thestructure and operation of the tourism sector. The results highlight the need for in-depthqualitative research on the social and cultural impacts of this transformation, as well as forpromoting sustainable and inclusive tourism development.